Numerical Analysis of Joule Heating Behavior and Residual Compressive Stress around Crack Tip under High Electric Load. (19th October 2017) - Liu, Thomas Jin-Chee
Abstract : This paper discusses the Joule heating effect and residual compressive stress near the crack tip under the electro-thermo-structural coupling state. For the crack tip field, the compressive condition is important for retarding or stopping the crack growth.